2014
DOI: 10.1021/mz5001288
|View full text |Cite
|
Sign up to set email alerts
|

Multiblock Copolymers by Thiol Addition Across Norbornene

Abstract: Multiblock copolymers, composed of different combinations and number of blocks, offer appreciable opportunities for new advanced materials. However, exploring this parameter space using traditional block copolymer synthetic techniques, such as living polymerization of sequential blocks, is time-consuming and requires stringent conditions. Using thiol addition across norbornene chemistry, we demonstrate a simple synthetic approach to multiblock copolymers that produces either random or alternating architectures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 46 publications
0
53
0
Order By: Relevance
“…This lamellar-in-lamellar structure is very similar to those found in multiblock copolymer self-assembly, [21][22][23][24][25][26][27][28][29] while the alternating and block copolymers in our copolymer blend system are much easier to be synthesized than that of asymmetric multiblock copolymers. [30][31][32] In this contribution, to explore the influence of system parameters such as segment distribution and segregation strength on phase separation, we design a series of polymer Monte Carlo simulations were carried out to study the phase separation of a copolymer blend comprising an alternating copolymer and/or block copolymer in a thin film, and a phase diagram was constructed with a series of composed recipes. The effects of composition and segregation strength on phase separation were discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…This lamellar-in-lamellar structure is very similar to those found in multiblock copolymer self-assembly, [21][22][23][24][25][26][27][28][29] while the alternating and block copolymers in our copolymer blend system are much easier to be synthesized than that of asymmetric multiblock copolymers. [30][31][32] In this contribution, to explore the influence of system parameters such as segment distribution and segregation strength on phase separation, we design a series of polymer Monte Carlo simulations were carried out to study the phase separation of a copolymer blend comprising an alternating copolymer and/or block copolymer in a thin film, and a phase diagram was constructed with a series of composed recipes. The effects of composition and segregation strength on phase separation were discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…23,26 Often, multiblock copolymer synthesis requires a series of rigorous living polymerizations 27,28,29 although recent investigations using end-linking strategies have simplified multiblock synthesis. 23,26,30 In contrast to equilibrium structures, numerous groups have investigated methods to trap non-equilibrium bicontinuous morphologies formed as a result of spinodal decomposition. 31,32,33,34 Demixing is typically induced through solvent, 35 temperature, 36 or polymerization 37,38 induced phase separation, and coarsening of the bicontinuous morphology is then kinetically arrested using several routes including vitrification, 32 chemical cross-linking, 39 or jamming/gelation of nanoparticles.…”
mentioning
confidence: 99%
“…Tew and coworkers reported a successful synthesis of multiblock copolymers via dithiol small linkers to be reacted with α,ω-dinorbornene-end functional polymers in THF using photoinitiated thiol-ene technique. [19] On the other hand, Bowman group very recently reported that efficient thiol-ene click reactions for polymer-polymer conjugation strictly depend on a proper initiator and end group selection. [20] They achieved ≈91% efficiency in the conjugation of a thiol-terminated poly(ethylene glycol) (PEG) to a norbornene-terminated PEG in water using photoinitiated thiol-ene reactions.…”
Section: Click Reactionsmentioning
confidence: 99%
“…In this regard, there are a few exceptions reported in literature. Tew and coworkers reported a successful synthesis of multiblock copolymers via dithiol small linkers to be reacted with α,ω‐dinorbornene‐end functional polymers in THF using photoinitiated thiol‐ene technique . On the other hand, Bowman group very recently reported that efficient thiol‐ene click reactions for polymer–polymer conjugation strictly depend on a proper initiator and end group selection .…”
Section: Introductionmentioning
confidence: 99%